Pengaruh Kualitas Website Cepat Respon Masyarakat (CRM) terhadap Citra Pemerintah Provinsi DKI Jakarta (Survei Pada Pelapor WEB CRM Kelurahan Cilandak Barat) - Qurotul Putri Riyadi; Sa’diyah El Adawiyah (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The DKI Jakarta Provincial Government through Jakarta Smartcity presents the CRM (Quick Community Response) website as a means for public complaints regarding various environmental issues, as well as a form of implementing modern, transparent, and public service-oriented governance, as well as an effort to build positive government relations and image with the public. This study aims to measure the quality of the CRM website, the image of the DKI Jakarta Provincial Government through CRM implementation, and the influence of CRM website quality on the government's image. The population in this study were CRM web reporters in Cilandak Barat Village with a sample of 82 people. The study used the WebQual 4.0 theory (Barnes and Vidgen in Nugroho, 2016), and image theory (John Nimpoeno in Mubarok, 2023) with a quantitative method through a survey of 82 respondents using a questionnaire. The results of this study indicate that the quality of the CRM website and the image of the DKI Jakarta Provincial Government are considered good by respondents. Based on the results of the research that has been conducted, it can be concluded that the quality of the CRM (Quick Community Response) website can be said to be positive, unidirectional and significant. In addition, the quality of the CRM website influences the image of the DKI Jakarta Provincial Government by 59.4%.